1994
DOI: 10.1037/0735-7044.108.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Relation of spatial learning of rats in the Morris water maze task to the number of viable CA1 neurons following four-vessel occlusion.

Abstract: Male Wistar rats were tested in the Morris water maze task 1 week after 6, 9, or 12 min of transient global ischemia. The 9-min and 12-min ischemia groups were significantly impaired in the acquisition and the reversal experiment. A systematic counting of CA1 neurons in the whole hippocampal formation revealed a unilateral number of CA1 neurons of 286,000 in the sham group, of which 2/3 were located in the dorsal hippocampus. The ischemia groups showed a significant decline in the number of dorsal CA1 neurons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 41 publications
7
50
1
Order By: Relevance
“…Global cerebral ischemia, which leads to the most extensive neuronal damage in the CA1 layer of the hippocampus, results in a deficit in spatial learning and memory. 18,19 The water maze, introduced by Morris 12 in 1984, reveals an impairment in spatial learning and memory that is easily quantified. Thus, it is useful for investigating whether neuroprotective strategies that reduce neuronal damage also lead to functional improvements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global cerebral ischemia, which leads to the most extensive neuronal damage in the CA1 layer of the hippocampus, results in a deficit in spatial learning and memory. 18,19 The water maze, introduced by Morris 12 in 1984, reveals an impairment in spatial learning and memory that is easily quantified. Thus, it is useful for investigating whether neuroprotective strategies that reduce neuronal damage also lead to functional improvements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 10 minutes of ischemia impairs rat learning and memory. 18,19 Some neuroprotective strategies that decrease neuronal death also attenuate the learning and memory deficit. 20,21 In this study, we also found that ischemic postconditioning, which decreased neuronal cell death, also reduced escape latency and increased the time spent during the probe test in the quadrant where the platform had been.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that rats with hippocampal or frontal lobe damage perform poorly on this task [34,35], the MWM has also proven valuable in revealing the anatomy, physiology and pharmacology of spatial learning and memory more generally [36][37][38]. It has also proven to be a useful tool for measuring deficits, treatment and recovery after various forms of brain injury [39][40][41][42][43] and has been used for the development of animal models of TBI [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a long-term progressive continuous plastic reorganization of the dendritic tree and dendritic spines, initially altered by acute global cerebral ischemia, has been shown to occur in pyramidal neurons at layers 3 and 5 of the sensorymotor cortex of the rat (Akulinin et al, 1997(Akulinin et al, , 1998(Akulinin et al, , 2004. Thus, preservation or recovery of hippocampal-and pre-frontal cortex-dependent functions after global cerebral ischemia, may involve long-term cytoarchitectural modifications in those remaining hippocampal CA1 and prefronto-cortical (layers 3 and 5) pyramidal neurons, since their morpho-functional organization is critical for normal learning and memory performance (Block, 1999;McDonald & White, 1993;McNamara & Skelton, 1993;Olsen et al, 1994;Olvera-Cortés et al, 2002;Silva et al, 1998), on the basis of the major role played by the CA1 region for the output of information flowing through the hippocampus, via the tri-synaptic circuit (Herreras et al, 1987). It is well known that the prefrontal cortex is directly involved in the organization of sequenced motor actions during working-memory performance (Fuster, 1999;I.…”
Section: Cellular Mechanisms Of Neuronal Plasticity and Repairmentioning
confidence: 99%
“…The magnitude and type of cognitive deficits in experimental animals submitted to global cerebral ischemia may vary considerably depending on the animal model, the survival times of testing, and the specific behavioral tests that could have been used. Among these procedures to evaluate cognitive functions, the Morris water maze, the eight-arms radial Olton maze, and the T maze, have been widely used in assessing learning and memory in both 2VO and 4VO models in rats, and its correlation with neuronal loss (Block, 1999;Hartmann et al, 2005;Olsen et al, 1994;Volpe et al, 1984), and functional and morphological characteristics of the neural substrate underlying cognitive functions in brain structures vulnerable to ischemia. Novel object recognition tests have been shown to be a reliable index of cognitive functions since rats or mice normally spend more time exploring novel objects, whereas animals with recognition memory deficits will explore novel and familiar objects equally (Hartman et al, 2005).…”
Section: Cognitive Functions Assessmentmentioning
confidence: 99%